Pengaruh Pelatihan dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan dengan Motivasi Sebagai Variabel Intervening (Studi Kasus PT. Tunas Dwipa Matra Mojosari) - Septifana Rosiani; Eny Setyariningsih; Kasnowo Kasnowo (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Training and development of human resources (HR) is very important for every company to maximize the skills of its employees. The quantitative approach focuses on symptoms that have certain characteristics in order to observe the relationship between 2 or more variables. According to the results of the study with the PLS SEM test, descriptive analysis, and hypothesis testing, the results can be seen: training has a significant positive effect on employee performance when viewed from the results of p values, namely 0.019 <0.05. HR development has a significant positive effect on employee performance if you look at the p values of 0.000 <0.05. Job training has a significant positive effect on motivation from the hypothesis test, namely p values 0.002 <0.05. HR development has a significant positive effect on work motivation seen from the results of the hypothesis test, namely the p value of 0.000 <0.05. Motivation has a significant positive effect on employee performance seen from the hypothesis test, namely the p value of 0.002 <0.05